Examining the Recorded Histories of Nigeria's First Post-Independence Universities - Adefolatomiwa Toye (Docomomo Journal)
Nigeria’s independence ushered in an era of university creation. Four new universities were established by 1962, just two years after attaining self-rule. Twenty-five years later, they each commissioned and published a book that documented their histories. This article employs a textual analysis of these publications within the context of contemporary research on university architecture in 20th-century Nigeria. It examines these books as a historical source for tracing the universities’ architectural histories. It further explores the ways they documented their built environment through their accounts of academic development, institutional changes, and nation-building goals. Finally, it reflects on the relevance of their sources, narratives, and limitations in reimagining the architectural history of Nigeria’s first universities.